The Effectiveness of the Sweet Thumbs Innovation Service Regarding Electronic ID Card Ownership in Central Amuntai District, North Hulu Sungai Regency (Case Study of State Vocational High School 1 Amuntai and State Vocational High School 2 Amuntai) - Muhamad Arsyad; Arief Budiman; Isnawati Isnawati (Universitas Dharmawangsa Medan, 2026)
Abstract The Jempol Manis program, an innovative mobile E-KTP recording service at vocational schools in rural Kalimantan Selatan, faces an accessibility paradox: bringing civil registry services closer to productive-age students while hindered by low participation due to weak coordination and technical constraints. This qualitative case study aims to describe service effectiveness at two Amuntai Tengah vocational high schools and identify supporting-inhibiting factors from participants' experiential perspectives. Through triangulation of in-depth interviews, participatory observation, and document analysis with 13 informants (students, teachers, Dukcapil officers), data were thematically analyzed following the Miles & Huberman model using Campbell J.P.'s effectiveness theory lens. Findings reveal